Violencia parental y su influencia en el consumo de cannabis de un adolescente de 19 años del cantón Ventanas, Provincia de Los Ríos - Carriel Pérez, Lesley Melina (2022)
Cannabis use in adolescents arises regularly in today's society, this drug is considered the most consumed in the world. Adolescents are more vulnerable to ingestion than adults and the adverse effects are dependence, difficulties in psychosocial development, poor school performance, cognitive impairment and a tendency to develop depression and anxiety disorders, among others. The objective of the research is to analyze the influence that parental violence has on the consumption of cannabis in a 19-year-old adolescent. It should be noted that there are relatively few studies that examine parental violence as a risk factor for cannabis use in adolescents. Note that parental violence ranges from lack of family support and supervision, verbal, physical and psychological abuse to lack of healthy family models. The methodology of this research is qualitative, the methods used are case study and psychometric, the techniques used are psychological interview, clinical history, clinical observation, Beck depression inventory, Plutchik suicide risk scale, test assist v3.0 and test HTP version of Karen Rocher. An exhaustive bibliographical investigation and the psychological intervention of the case were also carried out. The proposed psychotherapeutic solution is based on Beck's cognitive behavioral therapy. It should be noted that as a result of the investigation it was determined that the patient has persistent depressive disorder also known as Distima and cannabis use as a result of parental violence experienced within the home. The conclusion confirms that parental violence has a severe influence and repercussion on the consumption of cannabis, and affects the optimal development of the patient at a social and academic level.